2020
DOI: 10.24875/ric.20000207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidities in Mexican SARS-CoV-2-Positive Patients: A Retrospective Analysis in a National Cohort

Abstract: Background:The coronavirus disease 2019 outbreak is a significant challenge for health-care systems around the world. Objective: The objective of the study was to assess the impact of comorbidities on the case fatality rate (CFR) and the development of adverse events in patients positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the Mexican population. Materials and methods: We analyzed the data from 13,842 laboratory-confirmed SARS-CoV-2 patients in Mexico between January 1, 2020, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
52
2
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 24 publications
14
52
2
16
Order By: Relevance
“…Similar to other studies, we found that older age is the main risk factor for dying from COVID-19, with every 10-year increase associated with the largest increases in hazard ratio [2,5,15]; in the PH-Covid19 score, 10-year increases added two points, starting from 30 years, and being <20 years subtracted 2 points. Sex (men), which increases two points in our score, was correlated with death in our study and others [2,3,5,6,15].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar to other studies, we found that older age is the main risk factor for dying from COVID-19, with every 10-year increase associated with the largest increases in hazard ratio [2,5,15]; in the PH-Covid19 score, 10-year increases added two points, starting from 30 years, and being <20 years subtracted 2 points. Sex (men), which increases two points in our score, was correlated with death in our study and others [2,3,5,6,15].…”
Section: Discussionsupporting
confidence: 81%
“…The coronavirus disease (COVID-19) pandemic is the global phenomenon which is shaping modern societies in the year 2020, a reason why the severe acute respiratory coronavirus 2 (SARS-CoV-2) has been named the once-in-a-century pathogen that scientists and global leaders had been worrying for [1]. Demographic and patient history risk factors for fatal outcomes in patients with COVID-19 have been characterized in large national cohorts [2][3][4][5], and broadly include old age, sex (men), comorbidities, deprivation (a correlate of poverty), and belonging to certain ethnic groups. Other clinical, radiological, and laboratory parameters at presentation have also been studied as risk factors for disease progression and death [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De otro lado, Hajifathalian et al [18] reportaron un RR: 1,58 (IC 95%: 1,18-2,13) de desarrollar distrés respiratorio comparado con no obesos en Estados Unidos y Qianqxian et al [22] indicaron un OR: 3,42 (IC 95%: 1,42-8,27) para el mismo desenlace en población China. Además, Simmonet et al [23] reportaron un OR: 7,36 (1,14) de necesidad de ventilación mecánica en personas obesas comparadas con personas con peso normal.…”
Section: Discussionunclassified
“…Luego de la lectura por títulos y resúmenes se excluyeron 124 estudios por no abordar los criterios de nuestra pregunta PICO (del inglés: patient, intervention, comparison, outcome); quedando 29 artículos para lectura a texto completo. Tras la lectura se excluyeron ocho artículos [8][9][10][11][12][13][14][15] por reportar únicamente obesidad como característica de la población general del estudio y 11 [15][16][17][18][19][20][21][22][23][24][25] artículos que por no reportar frecuencias o medidas de asociación entre obesidad y mortalidad (Figura 1). Al final, quedaron 10 artículos para esta revisión.…”
Section: Características De Los Estudiosunclassified